Route 1 Maine - Wright, Virginia M. (Maine Down East, 2013)
Meet the people and places--and hear the stories--that make the 527 miles of iconic U.S. Route 1 from Fort Kent to Kittery a unique and unforgettable experience.
Keywords: United States Highway 1; Maine -- Travel And Description